2005
DOI: 10.1111/j.1365-294x.2005.02506.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Mediterranean peninsulas: evidence of central European glacial refugia for a temperate forest mammal species, the bank vole (Clethrionomys glareolus)

Abstract: This study details the phylogeographic pattern of the bank vole, Clethrionomys glareolus, a European rodent species strongly associated with forest habitat. We used sequences of 1011 base pairs of the mitochondrial DNA cytochrome b gene from 207 bank voles collected in 62 localities spread throughout its distribution area. Our results reveal the presence of three Mediterranean (Spanish, Italian and Balkan) and three continental (western, eastern and 'Ural') phylogroups. The endemic Mediterranean phylogroups di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
337
6
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(371 citation statements)
references
References 77 publications
27
337
6
1
Order By: Relevance
“…Therefore, similar to other small mammals (Fløjgaard et al, 2009) the distribution of M. glareolus appears to be related to productivity in the environment (Stephenson, 1998). This result suggest that introgressed M. rutilus mitotype in M. glareolus background could have facilitated the invasion of this species to more severe environments, assuming that hybridization happened before the invasion (as suggested by some of the previous studies: Tegelström, 1987;Deffontaine et al, 2005). These evidences also suggest that different mitotypes (and likely also key OXPHOS nuclear units) populate different climatic regions that may have allowed local adaptation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Therefore, similar to other small mammals (Fløjgaard et al, 2009) the distribution of M. glareolus appears to be related to productivity in the environment (Stephenson, 1998). This result suggest that introgressed M. rutilus mitotype in M. glareolus background could have facilitated the invasion of this species to more severe environments, assuming that hybridization happened before the invasion (as suggested by some of the previous studies: Tegelström, 1987;Deffontaine et al, 2005). These evidences also suggest that different mitotypes (and likely also key OXPHOS nuclear units) populate different climatic regions that may have allowed local adaptation.…”
Section: Discussionsupporting
confidence: 72%
“…Whether massive mtDNA introgression results from purely neutral processes or it can be significantly affected by natural selection remains a matter of debate (Cheviron and Brumfield, 2009;Arnold et al, 2011;Pons et al, 2013). For example, studies on the Eurasian bank vole Myodes (or Clethrionomys) glareolus have shown that its northeastern, and some eastern, populations harbour an mtDNA lineage that introgressed from its neighbour, Myodes rutilus, that has even become fixed in some populations (Tegelström, 1987;Deffontaine et al, 2005;Boratyń ski et al, 2011). This observation led to the hypothesis that colonization of northeastern Europe and western Asia by M. glareolus was facilitated by the introgression (before or during colonization of currently occupied regions), through hybridization, of physiological mechanisms that allowed it to inhabit more severe habitats (Boratyń ski et al, 2011;Šíchová et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1). Similarly, some species such as the brown bear (Ursus arctos) (Taberlet et al, 1998) or different small mammal species [Clethrionomys glareolus (Deffontaine et al, 2005); Sorex minutus and S. araneus (Bilton et al, 1998) and M. arvalis (Jaarola and Searle, 2004) and M. oeconomus (Brunhoff et al, 2003)] display genetic lineages suggesting that these species also survived in more easterly refuges (the Caucasus or the southern Urals) and in Central Europe (Kotlı´k et al, 2006). Moreover, the examination of the fossil record of European temperate species during the last ice age (26000-13000 years ago) reveals that environmental conditions were not severe enough in these regions to prevent the survival of forest-dependent species, notably in Poland (Sommer and Nadachowski, 2006).…”
Section: Northern Refuge For Heligmosomoides Polish Populations?mentioning
confidence: 99%
“…Such species traditionally have been considered to have spread northwards from refugia in Southern Europe at the end of the glaciation (Hewitt, 1999). However, mitochondrial DNA studies on some widespread species of small mammal suggest that colonisation may have occurred from glacial refugia in central Europe (Bilton et al, 1998;Deffontaine et al, 2005). Chromosome studies on the common shrew suggest that postglacial colonisation of Northern Europe may have occurred from the Urals (Polyakov et al, 1997(Polyakov et al, , 2000 and from a refugium near the Black Sea coast along the northern slopes of the Carpathian Mts.…”
Section: Introductionmentioning
confidence: 99%